The Galician Beverage Picture Set (GBPS): A standardized database of alcohol and non-alcohol images - López-Caneda, Eduardo (2018)
The available picture sets in alcohol research are scarce and display a number of limitations, including poor picture quality, limited number of stimuli and absence of non-alcohol and/or real-life images. In the present study, we developed the Galician Beverage Picture Set (GBPS), a database of high-quality alcohol and non-alcohol pictures embedded in real-life scenarios.